Prediction of Preeclampsia by First Trimester Combined Test and Simple Complete Blood Count Parameters - Ayse Kirbas; Ali Ozgur Ersoy; Korkut Daglar; Turkan Dikici; Ebru Hacer Biberoglu; Ozgur Kirbas; Nuri Danisman (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Preeclampsia is a serious disease which may result in maternal and neonatal mortality and morbidity. Improving the outcome for preeclampsia necessitates early prediction of the disease to identify women at high risk. Measuring blood cell subtype ratios, such as the neutrophil to lymphocyte (NLR) and platelet to lymphocyte (PLR) ratios, might provide prognostic and diagnostic clues to diseases. Aim: To investigate hematological changes in early pregnancy, using simple complete blood count (CBC) and blood concentrations of beta-human chorionic gonadotropin (β-hCG) and pregnancy-associated plasma protein-A (PAPP-A) to determine whether these measures are of any value in the prediction and early diagnosis of preeclampsia. Materials and Methods: Six hundred fourteen consecutive pregnant women with preeclampsia (288 with mild disease and 326 with severe disease) and 320 uncomplicated pregnant women were included in the study. Blood samples for routine CBC and first trimester screen, which combines PAPP-A and free ß-hCG blood concentrations, were analyzed. Results: The NLR values were significantly higher in the severe preeclampsia group compared with the control group (p<0.001). We also confirmed that levels of PAPP-A were lower in patients who developed preeclampsia. Conclusion: Because measuring CBC parameters, particularly NLR, is fast and easily applicable, they may be used to predict preeclampsia.